Better photography. - Catling, Gordon (London Kaye & Ward, 1973)
Advice for choosing and operating a camera and its equipment, taking pictures, developing film, and earning cash from your camera.
Stamped on t.p.: Distributed by Sportshelf, New Rochelle, N.Y.
Keywords: Photography -- Juvenile literature; Photography